Epidemiological situation of dengue in Peru - Munayco, César V. (2023)
Dengue fever is a disease caused by the dengue virus and transmitted by the bite of the Aedes aegypti mosquito. Dengue generates explosive epidemics mainly related to the entry of a new serotype, loss of immunity in the population, climatic variability (“El Niño phenomenon”), and the persistence of dengue is related to vector abundance, social determinants, and inequalities. The country is currently experiencing an unprecedented dengue epidemic in the country's history that has spread to 20 regions and has been fueled by the presence of coastal “El Niño” and Cyclone “Yaku”.